Functional diversity of earthworm communities in forests in the south of the Russian Far East - Geraskina, Anna; Kuprin, Alexander (Ecological Questions, 2021)
Key species of soil macrofauna – large soil saprophages, i.e. earthworms – have been studied in unique in terms of floristic and faunal diversity, as well as the most preserved forests of the southern Russian Far East. The results of studying taxonomic and functional diversity of earthworms, their biomass and abundance and patterns of temporal spatial distribution in summer seasons, are presented. The complete set of the main functional groups of earthworms (epigeic, epi-endogeic, endogeic and anecic) was found only in the best-preserved valley forests, with no traces of logging and fires over the last century. The earthworm community is not complete (one or two functional groups are missing) in one of valley forest that was partially cut down and affected by fires in recent decades and in hillside forests. Horizontal spatial distribution was analysed for the epi-endogeic and endogeic groups of earthworms, dominating in terms of biomass and occurrence. It was found that, in the summer season, the group of epi-endogeic species showed the "covering" type of distribution (regular distribution without aggregation), whereas the group of endogeic species showed the "spotty" type of distribution (aggregated distribution).